The Effect Of Marigold Root Slices On Mosquito Avoidancein The Community Of Batu Galing Village (Journal of Namibian Studies : History Politics Culture, 2023)
The bite of the Aedes aegypti mosquito, which can cause dengue fever, eradicates the vector life cycle, by killing mosquito larvae, using fogging, abate powder, which have an effect on the environment. Researchers looking for natural larvicidal solutions that are safe and effective, researchers saw marigold plants in research sites. Marigold plants contain essential oils that are effective as larvicides in Culex quinquefasciatus mosquitoes, Anopheles stephensi and Aedes aegypti. This is a quasi-experimental study, a cross-sectional study design. The aim was to determine the effect of marigold root slices on the ability to avoid mosquitoes, as a repellent. The research location was in a room where mosquito nets were available, containing 110 mosquitoes. almost all (80%) found 88 evading mosquitoes and the remaining 22 (20%) mosquitoes alighted from a total of 110 mosquitoes in a mosquito net box with 1 gram of marigold root slices in under 5 minutes. The results of the Chi-square analysis obtained a P value = 0.04